Characterization of Klebsiella pneumoniae ST11 Isolates and Their Interactions with Lytic Phages - Tan, Demeng (Viruses, 2019)
The bacterial pathogen Klebsiella pneumoniae causes urinary tract infections in immunocompromised patients. Generally, the overuse of antibiotics contributes to the potential development and the spread of antibiotic resistance. In fact, certain strains of K. pneumoniae are becoming increasingly resistant to antibiotics, making infection by these strains more difficult to treat. The use of bacteriophages to control pathogens may offer a non-antibiotic-based approach to treat multidrug-resistant (MDR) infections. However, a detailed understanding of phage–host interactions is crucial in order to explore the potential success of phage-therapy for treatment. In this study, we investigated the molecular epidemiology of nine carbapenemase-producing K. pneumoniae isolates from a local hospital in Shanghai, China. All strain isolates belong to sequence type 11 (ST11) and harbor the bla(KPC-2) gene. The S1-PFGE (S1 nuclease pulsed field gel electrophoresis) pattern of the isolates did not show any relationship to the multilocus sequence typing (MLST) profiles. In addition, we characterized phage 117 and phage 31 and assessed the potential application of phage therapy in treating K. pneumoniae infections in vitro. The results of morphological and genomic analyses suggested that both phages are affiliated to the T7 virus genus of the Podoviridae family. We also explored phage–host interactions during growth in both planktonic cells and biofilms. The phages’ heterogeneous lytic capacities against K. pneumoniae strains were demonstrated experimentally. Subsequent culture and urine experiments with phage 117 and host Kp36 initially demonstrated a strong lytic activity of the phages. However, rapid regrowth was observed following the initial lysis which suggests that phage resistant mutants were selected in the host populations. Additionally, a phage cocktail (117 + 31) was prepared and investigated for antimicrobial activity. In Luria Broth (LB) cultures, we observed that the cocktail showed significantly higher antimicrobial activity than phage 117 alone, but this was not observed in urine samples. Together, the results demonstrate the potential therapeutic value of phages in treating K. pneumoniae urinary tract infections.